عبد الحسين حمد مطلك nuda.تاثير نقع حبوب الشعير بتراكيز مختلفه من استيل السالسليك (الاسبرين) على الاصابه بمرض التفحم السائب - ojs_admin; حمدعبد الحسين (University of Thi-Qar Journal of Science, 2019)
Four concentrates (0,1,2,3) mg Acetyl Salicylic Acid are used to know the effect on Barley loose Smut disease . Results shown that Acetyl Salicylic Acid effect on percent infection , the percent reach( 0%) in ( 3) mg concentration . The Correlation Coefficients are significant at 0.01 level between the levels of concentration and percent of infection . 53